THE MATHEMATIZATION OF COGNITIVE CONTENT AND THE IDEA OF UNIVERSAL LANGUAGE - Nijolė Aukštuolytė (Problemos)
The common tendency of the New Ages to search for exact methods of nature investigation brings out the mathematical reflection of the world. In the development of the cognitive content mathematization, the transformation of mathematics into a universal scientific method gave R. Descartes the idea of universal mathematics which deals with the common form of rational cognition, the latter being generalized into the idea of universal scientific language. The idea of universal language allowed him to not only obtain a mathematical model of organizing knowledge, but also a paradigm of the language capable of representing the world.